Flying fishes (Beloniformes: Exocoetidae) of the Socotra Archipelago with comments on status of Exocoetus socotranus Steindachner - Shakhovskoy, Ilia B.; Bogorodsky, Sergey V. (Zootaxa, 2021)
A checklist of the flying fishes found in the waters off Socotra Archipelago, northwestern part of the Indian Ocean, is provided based on published and original data. Thirteen species from five genera occur in the study area, and four more species found nearby. Keys for the species identification are provided. The type specimen of Exocoetus socotranus Steindachner, 1902 was examined and is determined to be a junior synonym of Cypselurus naresii (Günther, 1889).